(untitled) (Research, Society and Development, 2026)
Muscle fatigue is characterized by a reduction in the ability to generate force and is associated with neuromuscular and metabolic changes. During high-intensity exercise, the body undergoes several physiological stresses, such as muscle damage, dehydration, and glycogen depletion, which can impair performance when recovery is inadequate. The objective of this study is to analyze, based on the scientific literature, the effects of cold-water immersion on muscle recovery after resistance exercises.This study is characterized as a bibliographic review with a qualitative and descriptive approach, conducted through searches in the PubMed and Cochrane databases. English descriptors were used and combined using the Boolean operator AND, including terms related to cryotherapy, cold-water immersion, and muscle recovery. Studies published between 2020 and 2025 were included, involving human participants and focusing on sports physiotherapy, while duplicate studies or those not directly addressing the topic were excluded.The selection of studies was carried out through the reading of titles, abstracts, and full texts, followed by a descriptive analysis of the data. The results demonstrate that cold-water immersion is effective in reducing delayed onset muscle soreness and improving recovery between 24 and 96 hours after exercise, proving to be superior to passive recovery. The ideal application range is between 11 °C and 15 °C, with a duration of 10 to 15 minutes, while very low temperatures may be harmful. However, continuous use of this technique may negatively interfere with muscular adaptations, such as hypertrophy and strength gain.